GAMBARAN KARAKTERISTIK PASIEN GAGAL JANTUNG USIA 45 – 65 TAHUN DI RUMAH SAKIT PKU MUHAMMADIYAH GAMPING SLEMAN - Harigustian, Yayang; Dewi, Arlina; Khoiriyati, Azizah (IJNP (Indonesian Journal of Nursing Practices), 2016)
Heart failure is a disease that can caused death. About 5.1 million people in the United States had heart failure. In 2009, one in nine deaths caused by heart failure. In Indonesia, the prevalence of heart failure in 2013 was 0.13%, the estimated number of heart failure patients in Yogyakarta was 6,943 (0.25%). Based on data from 2007 indicated CHF Riskesdas the third cause of death in Indonesia after stroke and hypertension. The purpose of this study to determine the characteristics of heart failure patients in the Poly Heart Gamping Sleman PKU Muhammadiyah Hospital in September-November 2016. The study was conducted using a descriptive design. The sample was 32 respondents. Characteristics of patients with heart failure in Poly Heart PKU Muhammadiyah Hospital Gamping Sleman highest respondent's age range 61-65 years was 59.38%, the highest gender was female 53.12%, the last education was elementary 34.38%, the worst job many are civil servants was 31.25%, stage 2 was 93.75%. The conclusion of this study is that most of the respondents are at the age of 61-65 years old, the sex of the respondents is bigger than the male, the most recent primary school education, the work of most civil servants, and almost all respondents had heart failure stage 2. The results of this study are expected to be a reference to know the description characteristics of patients with heart failure so that prevention or intervention can be done to reduce the recurrence of patients with heart failure.